2010
DOI: 10.1016/j.jtcvs.2009.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Quality of mitral valve repair: Median sternotomy versus port-access approach

Abstract: In isolated posterior mitral valve pathology, quality of mitral valve repair with the port-access approach can compare with that with the conventional median sternotomy approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 17 publications
0
58
1
Order By: Relevance
“…Although there have been several reports focused on comparing the long-term freedom from reoperation between MICS and sternotomy, few studies demonstrated the long-term quality of the repaired MV (regurgitation or stenosis) and freedom from significant MR based on long-term regular echocardiographic follow-up. [8][9][10] In addition, previous studies have limitations for comparing outcomes between 2 groups, with significant differences in baseline characteristics. We, therefore, sought to compare the longterm clinical and echocardiographic outcomes of MV repair performed through a minithoracotomy versus a traditional sternotomy in a homogeneous population with degenerative MR using inverse-probability-of-treatment weighting (IPTW) to reduce baseline differences.…”
mentioning
confidence: 99%
“…Although there have been several reports focused on comparing the long-term freedom from reoperation between MICS and sternotomy, few studies demonstrated the long-term quality of the repaired MV (regurgitation or stenosis) and freedom from significant MR based on long-term regular echocardiographic follow-up. [8][9][10] In addition, previous studies have limitations for comparing outcomes between 2 groups, with significant differences in baseline characteristics. We, therefore, sought to compare the longterm clinical and echocardiographic outcomes of MV repair performed through a minithoracotomy versus a traditional sternotomy in a homogeneous population with degenerative MR using inverse-probability-of-treatment weighting (IPTW) to reduce baseline differences.…”
mentioning
confidence: 99%
“…Recent meta-analyses find comparable or superior results for the MICS approach [2,3]. A specific analysis of results in the elderly population is usually lacking, as most results either do not address this age group separately or include predominantly younger patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in excellent success rates and allows operating on higher risk groups including those with left ventricular dysfunction and reoperative scenarios. [6][7][8][9][10][11][12][13] While a very small number of centers have applied robotic technology and achieved equivalent results in the setting of posterior leaflet pathology, 14 a recent review echoes the voice of the majority of cardiac surgeons. In sharp contrast to urologic and obstetric surgery, the logistic, financial, and other constraints of the current generation of robotic technology have limited this approach.…”
Section: The Minimally Invasive Eramentioning
confidence: 99%